2012 12th International Conference on ITS Telecommunications 2012
DOI: 10.1109/itst.2012.6425293
|View full text |Cite
|
Sign up to set email alerts
|

Is CSMA able to coordinate multiple access in vehicular radio channels effectively?

Abstract: Abstract-The first generation of inter-vehicle communication networks will most likely be based on the IEEE 802.11p standard. That is, they are going to deploy Carrier Sense Multiple Access (CSMA) to coordinate channel access among neighboring vehicles. Recently, concerns have been raised that fast-fading propagation conditions, i.e. a time-and frequency-selective fading as reported by several measurement campaigns in highway environments, might challenge the effectiveness of CSMA. These concerns also lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The findings and results of existing works evaluation contained in Table V [64,66]. The review also shows that WAVE-based MAC protocol performs poorly in multiple access coordination as channel load approaches the maximum channel capacity [67].…”
Section: Congestion Control Techniques In Inter-vehicle Communicationmentioning
confidence: 99%
“…The findings and results of existing works evaluation contained in Table V [64,66]. The review also shows that WAVE-based MAC protocol performs poorly in multiple access coordination as channel load approaches the maximum channel capacity [67].…”
Section: Congestion Control Techniques In Inter-vehicle Communicationmentioning
confidence: 99%
“…Dai and Yamao proposed a probability analysis method that can predict packet delivery ratio for a multihop linear topology under fading environment, and they analyzed the impact of hidden terminal caused intraflow interference and compared two carrier sensing thresholds (−81 dBm and −85 dBm) [19]. Mittag and Hartenstein simulated V2V networks and they concluded that fading had only a slight impact on the effectiveness of CSMA [20]. Schumacher and Tchouankem showed that the severity of fading substantially influenced packet delivery based on their collected empirical data of highway traffic [21].…”
Section: Literature Reviewmentioning
confidence: 99%